Comparative efficacy and safety among high-intensity statins. Systematic Review and Meta-Analysis - Myriam Jaam; Hend Nasser Al-Naimi; Moumena Mahmoud Haddad; Dina Abushanab; Daoud Al-Badriyeh (Becaris Publishing Limited, 2023)
Aim: To summarize the evidence in terms of efficacy and safety of head-to-head studies of high-intensity statins regardless of the underlying population. Materials & methods: A systematic review and metaanalysis was conducted to summarize the effect sizes in randomized controlled trials and cohort studies that compared high-intensity statins. Results: Based on 44 articles, similar effectiveness was observed across the statins in reducing LDL levels from baseline. All statins were observed to have similar adverse drug reactions (ADRs), although higher dosages were associated with more ADRs. Based on a pooled quantitative analysis of atorvastatin 80 mg versus rosuvastatin 40 mg, rosuvastatin was statistically more effective in reducing LDL. Conclusion: This review further confirms that high-intensity statins reduce LDL by ≥50%, favoring rosuvastatin over atorvastatin. Additional data are needed to confirm the clinical significance on cardiovascular outcomes using real-world studies.